Effect of Trust, Price Fairness and Service Quality on Patient Satisfaction at the Dental Studio Clinic, Jakarta Barat - Stephanie Olivia; Innocentius Bernarto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze whether trust, price fairness and service quality have a positive and significant effect on patient satisfaction. This study uses a survey method. Data was collected using a questionnaire instrument. The target population in this study were all patients who had visited the dental studio clinic. The sampling method used is convenience sampling. The number of samples determined was 160 samples. The sampling technique was done by convenience sampling. Data analysis using PLS-SEM with SmartPls program. The results showed that trust (p-value 0.002), price fairness (P-value 0.000) and service quality (P-value 0.004) had a positive effect on patient satisfaction. Of the three variables, price fairness has the most dominant effect on patient satisfaction at the dental studio clinic.